2009
DOI: 10.1039/b913057h
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonium ionic liquids: design, synthesis and evaluation of biodegradability

Abstract: The biodegradability of a range of phosphonium ionic liquids (ILs) was assessed using the CO 2 headspace test (ISO 14593). Tetraalkylphosphonium cations in which one of the alkyl substituents contained ester, ether, alcohol or alkene functionality in order to promote biodegradation were targeted. These cations were paired with halide, triflimide and octylsulfate anions. In contrast to previously studied dialkylimidazolium and alkylpridinium ILs with incorporated ester moieties and octylsulfate anions, the phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(108 citation statements)
references
References 42 publications
4
100
0
4
Order By: Relevance
“…The two other ILs (i.e., tributyl-methylammonium methanesulphonate and butyltrimethylammonium methanesulphonate) reached 7 and 4%, respectively. In a CO 2 headspace test, also Atefi et al (2009) showed that ultimate biodegradation of various tri-n-hexylphosphoniumbased ILs in an aqueous medium after 28 days ranged from 0 to 30%, depending on the side chain functionality.…”
Section: Resultsmentioning
confidence: 97%
“…The two other ILs (i.e., tributyl-methylammonium methanesulphonate and butyltrimethylammonium methanesulphonate) reached 7 and 4%, respectively. In a CO 2 headspace test, also Atefi et al (2009) showed that ultimate biodegradation of various tri-n-hexylphosphoniumbased ILs in an aqueous medium after 28 days ranged from 0 to 30%, depending on the side chain functionality.…”
Section: Resultsmentioning
confidence: 97%
“…It is the anion that influences the hydrophobicity of ILs. Most of ionic liquids containing a chloride anion are miscible in water, while those comprising PF 6 -or N(CF 3 SO 2 ) 2 -are highly hydrophobic. A great advantage of ILs is their easiness to replace the anion that makes it possible to design compounds with required properties, suited to the particular system 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of ionic liquids containing a chloride anion are miscible in water, while those comprising PF 6 -or N(CF 3 SO 2 ) 2 -are highly hydrophobic. A great advantage of ILs is their easiness to replace the anion that makes it possible to design compounds with required properties, suited to the particular system 5,6 . It is the aim of this work to study the equilibrium of zinc(II) extraction from hydrochloric acid solutions with phosphonium and ammonium quaternary salts, and to apply them as carriers in polymer inclusion membranes.…”
Section: Introductionmentioning
confidence: 99%
“…8) [15,39]. Weder für Alkyl-noch für funktionalisierte Alkoxycarbonylmethyl-Verbindungen wurde ein signifikanter biologischer Abbau beobachtet.…”
Section: Phosphonium-verbindungenunclassified